COMPREHENSIVE ASSESSMENT OF THE DURABILITY OF WINDOWS MADE FROM DIFFERENT MATERIALS: WOOD, VINYL, ALUMINUM - Кликайло, Віталій (SWorldJournal, 2026)
The characteristics of the frame materials significantly affect the properties of the window. The window itself plays a decisive role in determining the overall energy efficiency of a building. This article analyzes four different types of frames: aluminu